Кинематическая эволюция зоны Пьенинских утесов в кайнозое (Украинские Карпаты) - Муровская, А.В.; Накапелюх, М.В.; Вихоть, Ю.М.; Шлапинский, В.Е.; Бубняк, И.Н.; Мычак, С.В. (Геофизический журнал, 2016)
Узагальнено дані щодо поверхневої, субповерхневої та глибинної будови зони П'єнінських скель (ЗПС). Наведено нові результати її геолого-структурного і тектонофізичного вивчення в межах української частини Східних Карпат. The data on surface, subsurface and deep structure of the Pieniny Klippen Belt (PKB) have been summarized and new results of its geological-structural and fault kinematic studies within the Ukrainian part of the Eastern Carpathians have been presented.